Effects of Lippia sidoides Cham. (Verbenaceae) essential oils on the honey bees, Apis mellifera (Apidae: Hymenoptera), foraging - Pinheiro, Izabella M. C.; S. Luz, João Henrique; N. Souza, Luis Flávio; Oliveira, Ana Cláudia; Oliveira, Eugênio E.; Aguiar, Raimundo Wagner; Santos, Gil R.; Ferreira, Talita P.; Silveira-Tschoeke, Marcela Cristina; Tschoeke, Paulo Henrique (Revista de Ciencias Agrícolas, 2019)
The use of plant essential oils has been adopted as less hazardous to the environment and human health than synthetic insecticides used for the control of insects that transmit diseases. Despite of exerting insecticidal activities against several insect disease vectors, the potential impacts on non-target organisms exerted by essential oils extracted from Lippia sidoides (Cham.) have not received adequate attention. Here, we evaluated the susceptibility and potential changes in consumption rates of honey bees, Apis mellifera (L.), when exposed to essential oils extracted from L. sidoides. Was exposed forager bees to honey syrup (50% v/v) containing L. sidoides essential oil for 5 h. After this exposure period, the bees received regular honey syrup for another 19 h period. Six essential oil concentrations was used, namely 1.0, 1.5, 2.0, 2.5, 3.0 and 3.5 µL of essential oil/mL of syrup, and evaluated the syrup consumption and bees mortality in both periods (at the 5th and 24th h). The results reveal that independent of the essential oil concentration, the forager bees fed significantly less on L. sidoides essential oil-containing honey syrup. However, feeding on L. sidoides essential oil-containing honey syrup did not cause significant mortality when compared with bees that were not exposed to the essential oils. Thus, the results demonstrate that L. sidoides essential oils exhibited adequate selectivity against honey bees.